Functional characterization of flower morphogenesis and senescence related genes using virus induced gene silencing technique in petunia hybrida - Siti Hajar Noor, Shaarani (2014)
In floricultural crops, flower morphology, such as large petals and double flower formation, and flower longevity are important factors that influence their quality. Petunia has been proved to be an excellent model plant for the study of flower development and senescence. However, even in petunia, there are a lot of genes whose function in flower development and senescence have not yet been characterized. Recently, techniques using virus induced gene silencing (VIGS) have been developed as efficient reverse genetics tools to test gene function. In this study, VIGS system that visualizes silencing induced-flower was established in petunia. Using this system, functional characterization of petunia candidate genes involved in flower morphogenesis and senescence was conducted. In parallel, identification and expression analysis of flower development related-genes that had not yet been identified in petunia was performed. Disadvantage of VIGS is that silencing is induced in a chimeric manner and it is sometimes difficult to identify flowers on which silencing is induced. To overcome the disadvantage of VIGS, system that use silencing of the chalcone synthase (CHS) gene, one of genes regulating anthocyanin biosynthesis, as a reporter to visualize silencing induced-flower was established. Tandem pTRV2 constructs containing a Ph-CHS fragment and target gene fragment(s) are prepared and agrobacterium cultures possessing these constructs are infiltrated onto petunia leaves of 2 to 3 weeks old seedlings. Five different petunia cultivars with blue or purple flowers, 'Cutie Blue', 'Fantasy Blue', 'Picobella Blue', 'Mambo Blue' and 'Mambo Purple' were infected with the construct and differences in silencing patterns. was observed among cultivars. In 'Cutie Blue' and 'Fantasy Blue' complete white flowers were observed as a results of silencing of Ph-CHS; however, no white color was noted in flowers or tissues in 'Picobella Blue', 'Mambo Blue' and 'Mambo Purple'. This indicated that effectiveness of this VIGS system differs dependent on flower genetic background. It is also revealed to be dependent on environmental factors such as temperature to get complete silencing phenotypes. Second, using the VIGS system, redundant function of two C-class MADS-box genes, pMADS3 and FBP6 genes on flower morphogenesis was revealed. In flowers induced by either pMADS3-VIGS or FBP6-VIGS, only small changes in commercial appearance were recognized regardless of cultivar, whereas in those induced by pMADS3/FBP6-VIGS, complete conversion of stamens into petaloid tissues and marked enlargement of upper limb- like tissues were observed, resulting in a decorative appearance in all the four cultivars. Moreover, cultivar-dependent conversion of carpels into new flowers was noted in pMADS3/FBP6-VIGS flowers. Of the four cultivars, only 'Mambo Purple' exhibited the development of new flowers instead of carpels and the emergence of ectopic new flowers from the axil of petaloid organs, which created an ornamental appearance with a high commercial value. Further, investigation of large and small petaloid stamens induced by pMADS3/FBP6-VIGS and pMADS3 -VIGS, respectively, revealed only small differences in cell size compared to the large difference in total surface area indicating that the sie of petaloid stamens in C-class genes suppressed flower was determined at early stage of flower development and the suppressed C-class gene function at the late stage of flower development has little influence on the final size of petaloid tissue. Third, function of genes encoding ethylene signal components, Ethylene Insensitive 2 (EIN2) and EIN3 like (EIL), on flower senescence was characterized. A cDNA encoding EIN2 (Ph-EIN2) and five cDNAs encoding EILs (Ph-EILJ to 5) were cloned from petunia petals and VIGS of these genes together with Ph-CHS were conducted. VIGS of all Ph-EILs were attempted at once by using a conserved region of the Ph-EILs. The flower longevity of VIGS-induced flowers was compared to those of non-VIGS flowers under the condition with or without pollination. The results showed prolonged longevity of VIGS-induced flowers indicating the involvement of Ph-EIN2 and Ph-EILs on petal senescence. When flowers were treated with propylene, an ethylene analogue, marked delay in petal senescence was observed in Ph-EIN2-VIGS flowers in comparison to non-VIGS flower. Thus, it has been clarified that Ph-EIN2 is functioning as ethylene signaling factor and involved in the petal senescence. Fourth, petunia orthologues of pollen formation-related genes Tapetum Determinant 1 (Ph-TPDJ) and Excess Male Sporocytes] (Ph-EMS]) were identified and their expression patterns during flower bud development were determined. Quantitative real time analysis of Ph-TPD] in stamen of flower buds at four different developing stages (5 mm to 15 mm in length buds) showed that Ph-TPDJ expression can be detected only in the youngest stage. Expression of Ph-EMS 1 was detected in stamen at all stages with highest expression at the youngest stage. Analysis in various tissues of the buds (sepal, petal, stamen and style) at youngest stage showed that Ph-TPDJ and Ph-EMS] are expressed not only in stamen but also in developing pistils and petals. In sepal, expression of Ph-TPD] was not detected, whereas expression of Ph-EMS] was detected at lower level than in the other tissues. These results suggest that Ph-TPDJ and Ph-EMS] cloned in this study interact with each other to regulate early steps of pollen development. It is also indicated that they are involved in development of style. The findings obtained in this study would be valuable for breeding new cultivars and developing technology to improve quality of petunia and other floricultural crops.